Description and Gradient analysis of the Coastal band Vegetation in the Groen River mouth area (Namaqualand Strandveld) - Raiomondo, Domitilla (Department of Environmental and Geographical Science, 2020)
Strandveld vegetation around the Groen river mouth was sampled using complementary ordination and classification techniques (DCA and TWINSP AN). Four communities can be recognised, although samples are primarily divided into inland and coastal plots. Two inland communities are: Stoebaria utilis-Salvia lanceolata community, characterised by tall vegetation(> 1m), on deep, loose soils; Hermannia spp-Leserlia diffusa community of short (<0.6m) vegetation on shallow soils with a hardpan dorbank layer. Two coastal Strandveld communities are: Vanzylia amulata-Limonium peregrinum community which has short vegetation ( <0.5m) on characteristic shallow soils with a calcrete layer at 50 cm deep; Ruschia hutchensonia-Sasola nolothensis community characterised by deep alkaline soils. Of the environmental variables sampled, soil resistance and the presence of calcium carbonate in the soil best explain the distribution of plots and species in ordination space. Communities classified in this study differ subtly from the Tall, Medium and Short Strandveld communities and Strand communities proposed by le Roux and Boucher, 1989 and 1993.